Availability and utilization of library portal services for research in Selected University libraries in Nigeria - Ejikeme, Anthonia Nwamaka; F., Obayi Uche; Ukamaka, Eze Jacintha (International Journal of Knowledge Content Development & Technology, 2021)
This research paper delved into the availability and utilization of library portal services for research in University libraries in Nigeria. Two research questions and two null hypotheses were formulated to guide the study. A structured questionnaire was used for data collection. The study was carried out in Nnamdi Azikiwe Library, University of Nigeria Nsukka (UNN) and Felix Aghagbo Nwako Library, Nnamdi Azikiwe University Library (UNIZIK), Awka. A total of 70 professionals (librarians and system analysts) in these libraries supplied data for the study. Data collected was analyzed using mean and standard deviation. These were used to answer the research questions while the null hypotheses were tested using t-test statistic at 0.05 level of significance and 68 degree of freedom. Major findings showed that portal Services available in the Library showed that the areas of availability of library portal services in Nnamdi Azikiwe Library, U.N.N. includes agriculture, health sciences, engineering, environmental sciences and information about institution, social sciences, arts and humanities, natural sciences. In Festus Aghagbo Nwako library, Awka, the areas of portal library services include career development, federal government programmes, environmental science, biological sciences, social sciences, arts and humanities, engineering, and health sciences. Findings on extent of utilization of portal services available in the libraries indicated that portal services are utilized to a low extent in the university libraries. Furthermore, Librarians did not significantly differ in their opinions on the availability of library portal services and on the extent of utilization of library portal services in the libraries under study. It is therefore recommended that provisions should be made by the universities and library management to provide and update required portal services in addition to creating enabling environment for enhanced access and utilization of these services. The governments must make effort to provide funds for policy implementation, necessary technology training for librarians and users, and develop general information infrastructure. URL: http://ijkcdt.net/xml/28378/28378.pdf